Partial slip effect on heat and mass transfer of MHD peristaltic transport in a porous medium - Obaid Ullah Mehmood; Norzieha Mustapha; Sharidan Shafie; T. Hayat (Universiti Kebangsaan Malaysia, 2014)
This research looks at the effects of partial slip on heat and mass transfer of peristaltic transport. The magnetohydrodynamic (MHD) flow of viscous fluid in a porous asymmetric channel has been considered. The exact solutions for the stream function, longitudinal pressure gradient, longitudinal velocity, shear stress, temperature and concentration fields are derived by adopting long wavelength and small Reynolds number approximations. The results showed that peristaltic pumping and trapping are reduced with increasing velocity slip parameter. Furthermore, temperature increases with increasing thermal slip parameter. Moreover, the concentration profile decreases with increasing porosity parameter, Schmidt number and concentration slip parameter. Comparisons with published results are found to be in good agreement.